Veterinary approaches to canine mammary tumors and knowledge of the consensus statement in Brazil - Zuchi, Tainá Luana Vieira Lopes; Lopatini, Cláudia Luana; Faria, Joice Lara Maia (Brazilian Journal of Veterinary Pathology, 2021)
Mammary gland tumors are one of the most commonly diagnosed tumors in female dogs, with a reported prevalence ranging from 26 to 73% in Brazil. In recognition of the importance of these tumors veterinary researchers and clinicians in Brazil produced the first consensus statement regarding canine mammary tumors in 2010. The intention was to establish criteria for diagnosis, prognosis, and treatment. This study evaluated the methods of prevention, diagnosis, treatment, and determination of prognosis used by veterinarians in Brazil, and sought to quantify the number of veterinarians who were aware of the consensus statement. One hundred and three veterinary clinics participated in the study, 87.37% of which recommend early neutering as a preventative treatment for mammary tumors. For diagnosis, 100% of these use laboratory testing, 94.17% perform chest radiography, 78.64% incisional biopsies, 44.66% cytological analysis, and 13.59% immunohistochemical analysis. The most common surgical procedure is unilateral mastectomy (72.81%), and chemotherapy is performed in 49.51% of the clinics. Of the 103 clinics, 66.01% were aware of the consensus. Although knowledge of the consensus statement is widespread among veterinarians in Brazil, not all its recommendations are being followed. Preventive actions for canine mammary tumors are well established in most parts of the country. However, the consensus statement has had little influence on informing prognostic and therapeutic approaches, with a poor uptake of surgical removal of lymph nodes and immunohistochemical examination.